2019
DOI: 10.1177/0885328219877584
|View full text |Cite
|
Sign up to set email alerts
|

In vivo comparison of a granular and putty form of a sintered and a non-sintered silica-enhanced hydroxyapatite bone substitute material

Abstract: Improved handling characteristics of bone substitute materials may facilitate surgical handling. However, the respective modifications should not alter the biological activity. For comparison of a granular and a putty form of two silicaenhanced bone substitute materials, in 30 rabbits, bilateral bone defects were created in the femoral condyle and randomly filled with (1) sintered, silica-enhanced (0.8 wt%) hydroxyapatite (ACg, n ¼ 15); (2) ACg plus resorbable polymer (ACp, n ¼ 15); (3) non-sintered silica-enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Previous studies have shown that non‐sintered BSM exhibits an increased formation of new bone compared with sintered BSM 34 . This might be explained by the higher percentage of pores facilitating the ingrowth of new bone and blood vessels 35,36 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that non‐sintered BSM exhibits an increased formation of new bone compared with sintered BSM 34 . This might be explained by the higher percentage of pores facilitating the ingrowth of new bone and blood vessels 35,36 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that non-sintered BSM exhibits an increased formation of new bone compared with sintered BSM. 34 This might be explained by the higher percentage of pores facilitating the ingrowth of new bone and blood vessels. 35,36 The BSM used in the present study is known to have a chiseled-ruffled, large surface with a mean pore size distribution of 330-530 μm representing the optimal pore size for osteoconduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main prerequisites for ideal BSM are both ease of its handling and application as well as biological characteristics close to autologous bone. 42 Considering that, allograft may be the BSM of choice, due to its unlimited availability, possibility of patient specific customization and its biocompatibility. Generally, ABSM has the potential to induce endochondral bone formation, that is feasible by incorporated BMPs and collagen type I, [43][44][45] although limited in comparison to autologous bone.…”
Section: Discussionmentioning
confidence: 99%
“…A number of calcium phosphate-based synthetic bone graft substitutes have been developed in the last decade that build upon the traditional concepts of synthetic bone graft technology. These include the development of chemically modified calcium phosphates [11], incorporation of a submicron surface topography to the granules [1,3] and using nanoscale materials in manufacturing the bone graft [12]. The efficacy of such materials is typically evaluated by comparison to autograft in a pre-clinical model of posterolateral spinal fusion [5,6,[13][14][15], using the validated Boden model in rabbits that shows fusion rates with autograft that are similar to this in humans [16].…”
Section: Introductionmentioning
confidence: 99%